A STUDY ON READING ABILITY OF SCIENCE DEPARTMENT STUDENTS OF TEACHER TRAINNING AND EDUCATIONN FACULTY-UNIVERSITY OF RIAU - Ramadhani, Aulia; Novitri, Novitri; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this study is to discover the reading ability of Science Department students of Teachers Training and Education Faculty-University of Riau. The design of this study is quantitative research. This study used reading TOEFL equivalent as instrument of this research which consist of 50 questions. The sample of this research is Science Department Students in the 2016 academic year, namely Biology, Chemistry, Physics and Math, and there were 266 students involved. The result shows that Physic department student gained the highest average score (73.68) and Math Department Student reached the lowest average score (68.74). This study concluded that the reading ability of Science department students of teacher training and education Faculty University of Riau in the 2016 academic year is in poor level. The implication of this research, it is suggested that the students need to improve their reading ability by doing practicing on comprehending of TOEFL reading materials.Key Words: Ability, Reading, Science Department Student